2016
DOI: 10.16965/ijar.2016.209
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Pedicles of the Lumbar Vertebrae in Adult Punjabi Males

Abstract: Background: Pedicles of lumbar vertebrae are commonly fractured especially in older age group due to osteoporosis and need surgical screws fixation for stabilization of vertebrae. Different studies are being conducted in different populations to know the normal range of pedicle diameters. These diameters can guide the clinicians approaching lumber vertebra pedicles for trans pedicular screw fixation. Aim of study: was to study the vertical, horizontal and interpedicular diameters of pedicles of lumbar vertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Studies have also claimed that the thickness of right and left pedicles were almost same 23,24 which is also supported by the results of the current study. A significant difference between the pedicle thickness of males and females were also reported in a study 8 which is inconsistent with this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Studies have also claimed that the thickness of right and left pedicles were almost same 23,24 which is also supported by the results of the current study. A significant difference between the pedicle thickness of males and females were also reported in a study 8 which is inconsistent with this study.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, a study reported, the pedicle breadth gradually increases from L1 to L3 vertebrae and slightly decreases at L4 and L5 vertebrae among adult Punjabi males 24 . Another study also reported that the breadth of the pedicle gradually increases from L1 to L3 vertebrae and again decreases at L4 and L5 25 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…MORPHOMETRIC STUDY OF PEDICLES OF DRIED ADULT HUMAN LUMBAR VERTEBRAE IN UDAIPUR ZONE.decrease from L1 to L2 and then decreased from L2 to L5, width of pedicle increase from L1 to L5 and interpedicular distance is gradually increase. So we can say that the findings are almost same[19]. JaskaranSingh et al (2014) The study was done on 20 cadaver and twelve parameters of vertebrae were measured.…”
mentioning
confidence: 68%
“…The values of the PW in our study are comparable to some studies; 2,6,12 however, few studies have documented smaller values 11,16 while many studies have shown higher values as compared to ours. 8,13,17 Some authors have noted a much smaller values in some of their specimens at L1 11,14 and a much higher value at L5 level. 13,16,18 L2 and L5 vertebra on the left side had the lowest (5.38 mm) and highest (15.04 mm) value of pedicle width in our study.…”
Section: Discussionmentioning
confidence: 93%